Sounds in the urban square: qualitative influences on users’ lives - Machado , Cristiane Calzavara; Alberto, Klaus Chaves; Barbosa, Sabrina Andrade (Revista Nacional de Gerenciamento de Cidades, 2022)
Noise pollution is a worldwide public health problem that directly influences the population’s quality of life. The study of the soundscape in public spaces seeks to identify the perceptions of users and how it influences the experience in a given place. Thus, the aim of this study is to characterize the soundscape of Parque Halfeld square in Juiz de Fora, indicating how visitors assess the acoustic quality of this space. From on-site sound pressure levels measurements in the square and application of a questionnaire about the sound perception based on the Swedish SSQP (Swedish Soundscape-Quality Protocol), the results address the noise levels and the relationships between the users’ characteristics and the types of sounds perceived, as well as the related feelings. This study indicates that age, reason, and frequency of visits are some of the factors that most influence the perception of the soundscape and central areas of the square, a region with lower levels of sound pressure, are more pleasant in acoustic aspects. The questionnaire applied is also a contribution of this study to future research in the country. Given the pandemic scenario and the greater use of open spaces, this study can contribute to the planning of squares based on people’s perception of the soundscape.